Tales of Their Times - Rósa Þorsteinsdóttir (Humanities)
The aim of the article is to examine how the fairytales of storytellers from different times agree with the idea that their attitudes towards life appear in the fairytales that they tell and to consider whether they construct their fairytales so that they reflect the tensions and conflicts in their own times. This is achieved by looking into the tales of a woman storyteller in the nineteenth century when organized collecting began in Iceland, and three storytellers‘ repertoires from the twentieth century, when fairytales still belonged to the living oral tradition were tape-recorded. The survey is concluded by examining three recent plays involving fairytales which the author herself attended.